On the reversibility of legal consequences of a preventive security policy: The lifelong entry ban for potential terrorists as violation of the constitutional law and European law ZUR REVERSIBILITäT VON RECHTSFOLGEN EINER VORSORGENDEN SICHERHEITSPOLITIK - Wiater, Patricia (Die Verwaltung, 2019)
Since the terrorist attack on Berlin’s Breitscheidplatz took place in December 2016, German state interior ministries deport potential top terrorists in the accelerated procedure under section 58a Residence Act (AufenthG). As a legal consequence, section 11(5) Residence Act imposes a lifelong entry ban to foreigners who have been deported on the basis of § 58a Residence Act. In defining the requirements for deporting potential top terrorists, the ministries do not refer to the foreseeability of a concrete terrorist attack, but to the risk arising from the person concerned. Consequently, deportation orders can also be issued to persons who, although identifying with radical extremist Islamism, would not have committed terrorist attacks in case they had stayed in Germany. This practice of accepting misjudgements, that is of deporting „the wrong“, for the sake of public security forms part of the broader concept of fighting terrorism pre-emptively. The paper reveals that there is a twofold need for reform of the German lifelong entry ban for potential top-terrorists: It arises, on the one hand, from the fact that section 11 Residence Act violates EU law requirements of the „Return Directive“and, on the other hand, from the constitutional principle of proportionality. De lege lata, this principle is infringed because the legal consequence of a lifelong entry ban does not mitigate the deliberate acceptance of misjudgements within the framework of section 58a Residence Act. The paper argues that the constitutionality of pre-emptive security policy presupposes that the factual and legal consequences of misjudgements are reversible. As a consequence, the constitutionality of section 11 Residence Act with regards to potential top terrorists depends on setting time limits on entry bans.
CRIS-Team Scopus Importer:2023-03-21